Legislation - Malaysia, Gov of (Journal of Malaysian and Comparative Law, 1983)
The following list of Acts passed in Malaysia is a continuation of the list of Federal Acts contained in Vol. 9, Parts 1 & 2 (1983) J.M.C.L. 173 -175.